Double pass optical amplifier. - Abdullah, Mohammad Khazani; Mahdi, Mohd Adzir; Bouzid, Belloui; Endut, Rosdisham (2003)

(untitled)
A double pass optical amplifier comprises a first three port circulator (1) having an input signal port connected to at least one pumping laser (2) and an output signal port and a third port connected to one end of a length of doped optical fibre (4),a second three port circulator (5) connected to the other end of the length of doped optical fibre (4) and a loop of undoped optical fibre (6) incorporating at least one band pass filter (7), for allowing passage only of the input signal or signals and filtering out the amplified spontaneous emissions from the doped optical fibre (4), connected between the other two ports of the second circulator (5) to direct the filtered signal back through the length of doped optical fibre (4) to the output signal port of the first circulator.